Best Answer

6b^2 - 3b / 3b

6b^2 - 1

or

( 6b^2 - 3b) / 3b

= 2b - 1

Or

(6b^2 - 3b ) / 3b =

3b(2b - ) / 3b

= 2b - 1

Lvl 15

More answers

2b - 1

Q: 6b squared minus 3b divided by 3b?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3b+6b=9b

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

6+7a+6b

It is 17b when simplified

12a + 6b + 6c = 6(2a + b + c)

Related questions

3b+6b=9b

6(b - ac + b2 - bc)

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

6(ab - ac + b2 - bc)

5b - 3 - 2b = 6b - 3 3b - 3 = 6b - 3 3b - 6b = 3 - 3 b = 0

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b

6+7a+6b

b3 - 5b2 + 12 = (b - 2)(b2 - 3b - 6)Check:(b - 2)(b2 - 3b - 6)= b(b2 - 3b - 6) - 2(b2 - 3b - 6)= b3 - 3b2 - 6b - 2b2 + 6b + 12= b3 - 5b2 + 12

3b-4-6b-5

It is 17b when simplified

2 x (2a + 3b - 6)